AlphaFold-based AI docking reveals AMPK/SIRT1-TFEB pathway modulation by traditional Chinese medicine in metabolic-associated fatty liver disease - Lulu Zhang; Yi Zheng; Mingyan Shao; Aiping Chen; Meiyi Liu; Wenlong Sun; Tianxing Li; Yini Fang; Yang Dong; Shipeng Zhao; Hui Luo; Juan Feng; et al. (Pharmacological Research)
Metabolic-associated fatty liver disease (MAFLD) is a chronic, progressive disorder characterized by hepatic steatosis and excessive lipid accumulation. Its high global adult prevalence (approximately 50.7 %) is a significant concern worldwide. However, FDA-approved therapeutic drugs remains lacking. Qigui Jiangzhi Formula (QGJZF) shows promise in treating MAFLD by effectively decreasing lipid levels and improving hepatic steatosis, however its mechanisms remain unclear. This study investigated QGJZF’s effects in high-fat diet-induced zebrafish and golden hamsters, and in palmitate (PA) and oleic acid (OA) - induced HepG2 cells, using the SymMap database to identify potential targets and pathways of QGJZF in MAFLD and AlphaFold algorithms to predict protein structures. In vivo, QGJZF significantly alleviated hepatic lipid deposition. Intriguingly, QGJZF decreased lipid droplets and its levels are negative correlated with the numbers of autolysosomes, indicating that QGJZF’s mechanism of ameliorating liver lipid deposition may be related to the regulation of autophagy. QGJZF upregulated the expressions of phosphorylated -Adenosine 5‘-monophosphate (AMP) - activated protein kinase (p-AMPK), Sirtuin deacetylase 1 (SIRT1) and Transcription factor EB (TFEB), accompanied by the changes in autophagy-related proteins. In vitro, QGJZF inhibited the lipid deposition in PA/OA-stimulated HepG2 cells, and its effect was blocked by an autophagy inhibitor Baf-A1, which was mediated through upregulation of TFEB and its mediated autophagy-lysosomal pathway. Moreover, cotreatment with AMPK inhibitor Compound C, the regulation of QGJZF on TFEB, SIRT1, autophagy-related protein levels, and lipid deposition were reversed. Network pharmacology identified the PRKAA2 (AMPK) and SIRT1 as key hub targets. Futher analysis of their structures using AlphaFold3 algorithms, yielded high-ranking scores of 0.97 and 0.93, respectively. Liquid chromatography-mass spectrometry combined with molecular docking expounded its five compounds in QGJZF binding to AMPK protein. These findings suggest that QGJZF as a therapeutic agent in augmenting autophagy-facilitated lipid clearance for the management of MAFLD via AMPK/SIRT1-TFEB axis.